ANALISIS PENGARUH KUALITAS PELAYANAN DAN PENERAPAN PRINSIP - PRINSIP SYARI’AH TERHADAP KEPUASAN KONSUMEN HOTEL SYARI’AH X DI SEMARANG - Sugiyanto, Brigas Mahatmaloka; Adityawarman, Adityawarman (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2024)
Along with the growing development of the shari'ah economy in Indonesia, currentlythere are many institutions that apply shari'ah principles in running their business,one of which is shari'ah hotels. The thing that distinguishes Shari'ah hotels fromother hotels is in terms of the services and facilities provided reflecting Islamicvalues and religious nuances. Among them are that the hotel only provides halalfood and drinks, all employees wear clothes that cover their genitals, and provideprayer equipment in every hotel room. This study aims to determine how theinfluence of service quality and the application of shari'ah principles to consumerinterest in shari'ah hotels in Semarang. The method used in this research is aquantitative approach method. The population in this study are consumers andservice users of Hotel Syari'ah X in Semarang. Sampling using non-probabilitysampling technique with accidental sampling, amounting to 95 respondents.Meanwhile, the data collection method used in this study was a questionnaire thatwas measured using a Likert scale. In this study the data obtained were analyzedusing multiple regression with the help of the SPSS 24 application. From this study itcan be concluded that service quality has a positive and significant effect oncustomer satisfaction and the application of Shari'ah principles has a positive andsignificant effect on customer satisfaction. Likewise, simultaneously the variables ofservice quality and the application of syari'ah principles have a significant effect onthe variable of customer satisfaction at Hotel Syari'ah X in Semarang.